2017
DOI: 10.11114/jets.v5i5.2254
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Eight Grade Students about Transformation Geometry: Perspectives on Students’ Mistakes

Abstract: People need the idea of transformation geometry in order to understand the nature and environment they live in. The teachers should provide learning environments towards perceptual understanding in symmetry training and development practice skills of the students. In order to make up such a learning environment, teachers should have information about the mathematical structure of the concept of symmetry, the difficulties the students encounter while learning, misconceptions and the causes. Therefore, the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
2
8
0
2
Order By: Relevance
“…Thanks to this, and also from interviews from the pre-test, we know that the symmetry axis of the rhomboid is most often considered a horizontal median (those who answered "1" axis of symmetry), both medians (those who answered "2" axes of symmetry), or medians and diagonals (those who answered "4" axes of symmetry). Answer "2" was generally one of the most frequent incorrect answers, as in other research (Aktaş and Ünlü, 2017;Son, 2006). Leikin, Berman and Zaslavsky (2000) also encountered medians as the axes of symmetry of a rhomboid.…”
Section: Do Students Recognize That a Rhomboid Is Not An Axially Symmetrical Figure?supporting
confidence: 72%
See 2 more Smart Citations
“…Thanks to this, and also from interviews from the pre-test, we know that the symmetry axis of the rhomboid is most often considered a horizontal median (those who answered "1" axis of symmetry), both medians (those who answered "2" axes of symmetry), or medians and diagonals (those who answered "4" axes of symmetry). Answer "2" was generally one of the most frequent incorrect answers, as in other research (Aktaş and Ünlü, 2017;Son, 2006). Leikin, Berman and Zaslavsky (2000) also encountered medians as the axes of symmetry of a rhomboid.…”
Section: Do Students Recognize That a Rhomboid Is Not An Axially Symmetrical Figure?supporting
confidence: 72%
“…Here we can observe a misconception: 'a rhombus is an axially symmetrical figure.' Even worse results in research into the same problem were obtained by Aktaş and Ünlü (2017), who found that only 6.4% of respondents described a rhomboid as an axially asymmetrical figure.…”
Section: Do Students Recognize That a Rhomboid Is Not An Axially Symmetrical Figure?mentioning
confidence: 89%
See 1 more Smart Citation
“…Alanyazında sadece öğrencilerin değil öğretmen ve öğretmen adaylarının dönüşümler konusunda bilgi düzeylerinin yetersiz olduğunu belirten çalışmalar da (Ada & Kurtuluş, 2010;Al-Khateeb, 2016;Aktaş & Ünlü, 2017;Desmond, 1997;Gürbüz & Durmuş, 2009;Hacısalihoğlu-Karadeniz, Baran, Bozkuş & Gündüz, 2015;Harper, 2002;Kambilombilo & Sakala, 2015;Law, 1991;Mbusi, 2016;Son, 2006;Turgut, Yenilmez & Anapa, 2014) -Dönmede şekil üzerindeki her bir noktanın bir nokta etrafında belirli bir açıyla saat veya tersi yönünde dönüşüme tabi olduğunu ve şekil ile görüntüsünün eş olduğunu keşfeder.…”
Section: Introductionunclassified
“…Dönme hareketi programdan tamamen çıkarılarak yansıma ve öteleme hareketlerine yönelik kazanımlara ise sadece 8.sınıf düzeyinde yer verilmiştir. Ortaokul öğrencilerinin dönüşüm geometrisini öğrenmede zorluklar yaşadığını ve kavramları zihinlerinde yapılandırmakta güçlük çektiğini ortaya koyan bazı araştırmaların (Aktaş &Ünlü, 2017;Clements & Burns, 2000;Glass, 2001;İlaslan, 2013;Kaplan & Öztürk, 2014;Yanık, 2014) sonuçları dikkate alındığında, 2018 programında dönüşüm geometrisine daha az yoğunlukta ve güçlük düzeyi azaltılarak yer verilmesi yerinde bir karar olarak düşünülebilir. Mashingaidze (2012)' göre dönüşüm geometrisi matematik müfredatının biraz zor ve soyut kabul edilebilecek konuları arasındadır.…”
Section: Introductionunclassified